El Sueño como Factor Estimulante en la Calidad de la Atención en Enfermería - Caridad del Carmen Muñiz de Alfaro; Omar Hassaya Aranda Rodríguez (Ibero Ciencias - Revista Científica y Académica - ISSN 3072-7197, 2026)
Title: Sleep as a Stimulating Factor in the Quality of Nursing Care Introduction: Sleep is recognized as a basic physiological need; however, in the hospital setting, it takes on a strategic dimension because it directly influences the quality of care provided by nursing staff. This documentary research arises from the need to demonstrate how sleep deprivation affects professional performance, patient safety, and the sustainability of professional practice. Methodology: A documentary study with a qualitative approach was conducted, based on a systematic review of secondary scientific, regulatory, and academic sources published between 2015 and 2024. A bibliographic matrix was developed with 30 documents selected according to rigorous inclusion and exclusion criteria. The sources consulted were obtained from databases such as PubMed, Scopus, SciELO, Dialnet, and Google Scholar, prioritizing research related to occupational health, clinical performance, and sleep quality in hospital settings. Results: The findings revealed a direct relationship between sleep deprivation and a decline in the quality of nursing care. Effects such as an increase in clinical errors, impaired professional judgment, and reduced empathy and therapeutic communication were identified. Discussion: The analyzed data highlight the need to implement institutional models that recognize sleep as a fundamental component of nursing practice. Lack of adequate rest should not be understood solely as a consequence of work, but rather as a structural variable that affects the ethical, technical, and human performance of the profession.Conclusions: Sleep should cease to be considered an individual responsibility and become an institutional priority. Integrating adequate rest into occupational health policies, redesigning shift schedules, providing designated rest areas, and raising awareness about the importance of restorative sleep are urgent actions.